Exploring writing practices in two foundation phase rural multigrade classes - Blease, Bernita (Cape Peninsula University of Technology, 2014)
A full dissertation submitted in fulfilment of the requirements for the degree of Master in Education Presented to the Faculty of Education and Social Sciences at the Cape Peninsula University of Technology 2014 === Writing in rural multigrade Foundation Phase schools is a largely negelected area for research and teacher development. Even those teaching multigrade classes are not sure how to approach it. There are almost no regulations or guidelines in PIRLS or government documents and reports. Nevertheless multigrade rural schooling is prevalant throughout South Africa. This gap between widespread practice and lack of theoretical acknowledgement or knowledge prompted this study. For the purposes of this study two rural multigrade Foundation Phase classes were selected in the Northern District of the Western Cape. This study answers one main question: What writing practices are being implemented in these two rural Foundation Phase multigrade classes? Two sub-questions are: How do the two Foundation Phase teachers teach writing skills to rural multigrade learners? What challenges do these two Foundation Phase teachers experience when teaching writing? Lack of research in this area required considerable time to consolidate an appropriate research methodology. To establish a scientific structure for this research certain theoretical approaches were adopted. Socio-cultural theories of learning, particularly focusing on Bronfenbrenner’s socio-ecological model, Vygotsky’s Zone of Proximal Development (ZPD) and social constructivism were used. Piaget’s developmental contributions add to this research project. Cambourne’s principles and strategies were invaluable in understanding constructivism in a language classroom. Because this was a pioneering research project it took over four years to complete analysis of data from the schools and link it to the theoretical framework. A qualitative interpretative case study research design was specifically formulated to provide an objective understanding of the research questions. The data were analysed qualitatively. Four themes emerged from sub-question one and include: the pedagogy of teaching writing in a multigrade class, the importance of creating a writing ethos in the classroom, elements of writing and supporting learners in the writing process. The following six themes were identified in answering sub-question two: teacher challenges, poor socio-economic backgrounds, writing support from the WCED, creating a writing ethos including discipline, parental literacy and learner challenges. In conclusion, this research indicates that multigrade education is, far from being a recalcitrant problem or cause for apology, useful as a template for curriculum development in many other areas of education. Multigrade education provides a realistic and flexible tool for meeting urgent educational problems.